Evaluation of the utilization of external radiotherapy in the treatment of localized prostate cancer in Andalusia, Spain. Issue 1 (December 2015) - Expósito, José; Linares, Isabel; Castillo, Isabel; Martínez, Miguel; Vargas, Pilar; Herruzo, Ismael; Medina, José; Palacios, Amalia; Bayo, Eloísa; Peracaula, Francisco; Jaén, Javier; Sánchez, José; et al.
Abstract Background Around 27, 000 new cases of prostate cancer are diagnosed every year in Spain and 5400 die from this disease. Radiotherapy (RT), alone or combined, has proven to be effective as initial treatment in patients with localized disease. Our objective was to evaluate the use of external beam RT (EBRT) in our region, comparing the indication rate and irradiation rate and examining variability in its application among hospitals. Methods We conducted a review of RT guidelines and indication studies for prostate cancer (% expected irradiation). Data were gathered from all twelve public healthcare centers in Andalusia (Spain) on RT-treated prostate cancer patients during 2013 (% actual irradiation) and from nine of the centers on RT discharge reports. Information was classified according to type of hospital, tumor risk category and RT treatment (technique, dosage, volume, toxicity). Results The estimated RT rate was 67 % (1289/1917), 43 % were aged > 70 years, 44.7 % had ECOG performance status of 0); 44.7 % had high-risk tumors; 57 % underwent RT associated with hormone therapy; 70 % of patients receiving RT were treated with 3D planning (30 % IGRT); and doses were 70–76 Gy in 70 % of cases and >76 Gy in 10.7 %. Acute gastrointestinal and genitourinary toxicities were < grade 2 in 79 and 89 % of patients, respectively. An irradiation rate significantly below the mean for the study was found in four provinces. There was a significant difference among provinces in the distribution of risk groups. Conclusions Underutilization of EBRT was estimated to be around 30 % in prostate cancer patients, with an elevated variability in irradiation rates among hospitals related to differences in available technology and in the distribution of patients with different risk levels. These data should be a matter of concern to regional health managers, given the negative and measurable impact on the survival of patients.